Mobile application software development - Pereira, Ricardo Alexandre Gonçalves (2019)
The smartphone application industry has been on a steady rise all over the world, creating new jobs every year, in one of these companies I realised a 5-month internship in Sweden, developing a new feature for their app using React Native and Firebase. In this internship not only did I improved my programming skill but also gained invaluable insight on the industry, agile environments, how to better work as a team and the responsibility of developing a new feature for an established app on the market. In this dissertation I shall go over the history of the app, some stats of the industry, the agile methodology, the tools, frameworks and Services used to develop the feature I was trusted with, the day-to-day life of an agile developer in Equilab and how we overcame some issues.